Profitability And Firm Value: How Does Good Corporate Governance Affect Them? - Subiyanto, Bambang; Melati; Maulidya, Riska (CV ODIS, 2024)
This research was aimed at analyzing the intervention of Good Corporate Governance (GCG) on the influence of profitability on firm value. GCG was proxied by the audit committee, profitability was proxied by the Return on Assets (ROA) and Return on Equity (ROE), while firm value was proxied by Tobin’s Q. The analysis will be carried out using path analysis with SmartPLS on 105 observations from 21 manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange (IDX) in the 2017–2021 period. The results showed that ROA, ROE, and GCG have a significant positive effect on firm value. GCG has also been proven to be able to significantly intervene in the influence of profitability on firm value, with a positive relationship to ROA and a negative relationship to ROE.